Bicyclic Boronate VNRX-5133 Inhibits Metallo- and Serine-β-Lactamases - Krajnc, Alen (J Med Chem, 2019)
[Image: see text] The bicyclic boronate VNRX-5133 (taniborbactam) is a new type of β-lactamase inhibitor in clinical development. We report that VNRX-5133 inhibits serine-β-lactamases (SBLs) and some clinically important metallo-β-lactamases (MBLs), including NDM-1 and VIM-1/2. VNRX-5133 activity against IMP-1 and tested B2/B3 MBLs was lower/not observed. Crystallography reveals how VNRX-5133 binds to the class D SBL OXA-10 and MBL NDM-1. The crystallographic results highlight the ability of bicyclic boronates to inhibit SBLs and MBLs via binding of a tetrahedral (sp(3)) boron species. The structures imply conserved binding of the bicyclic core with SBLs/MBLs. With NDM-1, by crystallography, we observed an unanticipated VNRX-5133 binding mode involving cyclization of its acylamino oxygen onto the boron of the bicyclic core. Different side-chain binding modes for bicyclic boronates for SBLs and MBLs imply scope for side-chain optimization. The results further support the “high-energy-intermediate” analogue approach for broad-spectrum β-lactamase inhibitor development and highlight the ability of boron inhibitors to interchange between different hybridization states/binding modes.